No-panic pragmatism - Maarit Jaakkola; Jenny Wiik (Journalistica)
This chapter investigates the educational preparedness of Nordic academic journalism schools to teach artificial intelligence (AI) in 2024. More specifically, we examine journalism educators’ initial ideas on AI at a time when AI had gained prominence in public, following the release of the first user-friendly applications of generative and conversational AI. Based on the concept of pedagogical domestication of new technologies and journalism schools’ responsibility to critically adapt to industry development, we conducted a survey among journalism educators at major Nordic journalism education institutions (N=118, response rate 58%). We found that academic educators had mixed feelings about AI technologies. They expressed the need for AI to be incorporated primarily in the teaching of journalism ethics, as well as in fact-checking and information validation processes, but highlighted that the journalistic core values and understandings of the world needs to remain the same. With a mode of ‘no-panic pragmatism’, educators perceived AI as something that should be integrated into existing structures rather than anticipating a structural change in education. The study provides an initial documentation of the current state of journalism education and concludes with suggestions for further research and development of pedagogical practices.